The Distributional Effects of Oil Shocks - Tobias Broer; John Kramer; Kurt Mitman (Institute of Labor Economics (IZA), 2025)
Negative oil supply shocks since the 1980s have increased German inflation and reduced aggregate economic activity. Using 45 years of high-frequency German administrative data, we find that these shocks disproportionally harm low-income individuals: their earnings growth falls by two percentage points two years after a 10-percent exogenous oil price rise, while high-income individuals are largely unaffected. Job-finding probabilities for low-income workers also decline significantly. This contrasts with the distributional effects of monetary policy shocks, which, while also stronger at the bottom, primarily impact job-separation probabilities. To understand the role of monetary policy in shaping these outcomes, we analyze counterfactual scenarios of policy non-response. Because the actual policy response to oil shocks involves an initial rate rise followed by a fall, a fully anticipated non-response (McKay-Wolf, 2023) leaves the oil shock's aggregate and distributional effects little changed. When monetary policy repeatedly surprises by not reacting (Sims-Zha, 2006), in contrast, the implied initial monetary loosening dominates, boosting activity, inflation, and particularly employment prospects for low-income individuals.
Keywords: 330; monetary policy; inequality; Oil shocks; counterfactual